A CRITICAL DISCOURSE ANALYSIS OF TONY ABBOTT’S STATEMENTS RELATED TO THE SPYING ALLEGATION TOWARDS INDONESIA - Farhatun Nuuril Awwaliyah; Dwijani Ratnadewi (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
This research was done in 2014 when there was an issue of spying towards Indonesia by the Australian government. It explored Tony Abbott’s statements related to his countering the accusation towards the Australia government of the spying issue to Indonesia. The research aimed at answering Tony Abbott’s political discourse in his statements, finding the way he used the political discourse; finding the supposed reason of using the political discourse and seeking for the effects of this statements for Indonesia. Descriptive qualitative was applied as the approach of the research. Critical Discourse Analysis (CDA) proposed by Norman Fairclough was used as the main theory and Van Dijk’s theory of CDA is applied as the supporting theory. Data were taken from YouTube and transcribed; the data were enriched with the ongoing statements taken from Indonesian and Australian televisions. The results of the analysis showed that rhetorical strategy and power were always performed in his statements. This illustrated the way he used his political discourse. Explicitly, ideology was shown from his statements. His ideology was endorsing the activity of Australian Intelligence for the sake of National Security including the failure of stating apology towards Indonesia causing the disappointment and anger of the Indonesians to Australian Government. This result can be an evident of Fairclough’s viewpoint that ideology is inherent in the discourse.